2011
DOI: 10.1128/jvi.01189-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Ross River Virus Variant That Grows Persistently in Macrophages, Shows Altered Disease Kinetics in a Mouse Model, and Exhibits Resistance to Type I Interferon

Abstract: Alphaviruses, such as chikungunya virus, o'nyong-nyong virus, and Ross River virus (RRV), cause outbreaks of human rheumatic disease worldwide. RRV is a positive-sense single-stranded RNA virus endemic to Australia and Papua New Guinea. In this study, we sought to establish an in vitro model of RRV evolution in response to cellular antiviral defense mechanisms. RRV was able to establish persistent infection in activated macrophages, and a small-plaque variant (RRV PERS ) was isolated after several weeks of cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
(61 reference statements)
2
15
0
Order By: Relevance
“…However, in vitro type I IFN sensitivity assays demonstrated that both RRV-T48-nsP1 6M and RRV-T48-nsP1 S79C; L224I were more sensitive than RRV T48 to type I IFN. Recently, Lidbury et al described a mutant RRV (RRV PERS ) isolated from persistently infected murine macrophages (63). In agreement with our findings, in which sensitivity to type I IFN in vitro correlated with pathogenicity in vivo, RRV PERS displayed increased virulence in mice and increased resistance to type I IFN in vitro.…”
Section: Identification Of Virulence Determinants Within Nsp1supporting
confidence: 92%
See 1 more Smart Citation
“…However, in vitro type I IFN sensitivity assays demonstrated that both RRV-T48-nsP1 6M and RRV-T48-nsP1 S79C; L224I were more sensitive than RRV T48 to type I IFN. Recently, Lidbury et al described a mutant RRV (RRV PERS ) isolated from persistently infected murine macrophages (63). In agreement with our findings, in which sensitivity to type I IFN in vitro correlated with pathogenicity in vivo, RRV PERS displayed increased virulence in mice and increased resistance to type I IFN in vitro.…”
Section: Identification Of Virulence Determinants Within Nsp1supporting
confidence: 92%
“…In agreement with our findings, in which sensitivity to type I IFN in vitro correlated with pathogenicity in vivo, RRV PERS displayed increased virulence in mice and increased resistance to type I IFN in vitro. Five of the 12 amino acid differences between RRV T48 and RRV PERS were located in nsP1 (63). In addition, the mutations in nsP1 that arose during SINV passage in the presence of decreased levels of GTP also conferred enhanced sensitivity to interferon (49,64).…”
Section: Identification Of Virulence Determinants Within Nsp1mentioning
confidence: 99%
“…compared to a progeny production upper than 8 log PFU.mL -1 in HEK-293 and VERO cells (Lidbury et al 2011) ( Fig. 1B).…”
Section: Ross River Virus (Rrv) Is a Mosquito-borne Alphavirus Of Medmentioning
confidence: 99%
“…RRV is able to establish persistent infections in many cell lines including mouse muscle cell (Eaton and Hapel, 1976), human synovial fibroblasts (Journeaux et al, 1987) and macrophages cell lines (Linn et al, 1996, Way et al, 2002, Lidbury et al, 2011. CHIKV was found to have persisted in spleen macrophages in macaques months after CHIKV infection (Labadie et al, 2010, Messaoudi et al, 2013.…”
Section: Macrophages and Viral Persistencementioning
confidence: 99%
“…The ability of alphaviruses to acquire mutations and better evade the antiviral effects of IFNα/β have been reported (Lidbury et al, 2011, Stoermer Burrack et al, 2014 with CHIKV and other alphaviruses having evolved strategies to counter the host's type I and II interferon responses Klimstra, 2008, Fros et al, 2010). Virus isolated from Rag-1 -/-mice on 100 and 429 days post-infection behaved no differently from parental virus (with respect to viraemia and foot swelling) when isolated from blood, expanded in C6/36 cells, and used to infect WT mice (data not shown).…”
Section: Persistent Virus Recovered From Rag1 -/-Micementioning
confidence: 99%